Perkembangan Kognitif Manusia Dalam Perspektif Psikologi Dan Islam - Sokhibul Arifin (TADARUS, 2016)
AbstractCognitive development is part of the development phase of human characteristics that are important to learn. Psychologists have attempted to formulate about human cognitive development as noted by Piaget's theory of cognitive development stages of man, so is the theory of cognitive development by Lev Vygotsky, and the model of information processing as a part of cognitive development. However, Islam also gives the meaning of the concept of human cognitive development. Description of the Qur'an and hadith texts and the opinion of the scholars on the cognitive development of humans ought to be studied.